2019
DOI: 10.1029/2018ea000527
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of the Tropospheric Gradients Estimated With GPS During Hurricane Harvey

Abstract: During the last decade Global Positioning System (GPS) Continuous Operating Reference Stations networks have become a new important data source for meteorology. This has dramatically improved the ability to remotely sense the atmosphere under the influence of severe mesoscale and synoptic systems. The zenith tropospheric delay (ZTD) is one of the atmospheric variables continuously observed, and its horizontal variations, the horizontal tropospheric gradients, are routinely computed nowadays within the dual‐fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 45 publications
0
16
0
2
Order By: Relevance
“…Milliner et al (2018) were the first to monitor the amount of water drained by the ground from hurricanes across the Gulf and East Coasts of the USA. More recently, Graffigna et al (2019) showed a significant shift in ZTD gradients prior to the arrival of a hurricane. Ejigu et al (2020) assessed the connection between GPS-derived IWV and its influence on TC structure during Hurricane Florence in 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Milliner et al (2018) were the first to monitor the amount of water drained by the ground from hurricanes across the Gulf and East Coasts of the USA. More recently, Graffigna et al (2019) showed a significant shift in ZTD gradients prior to the arrival of a hurricane. Ejigu et al (2020) assessed the connection between GPS-derived IWV and its influence on TC structure during Hurricane Florence in 2018.…”
Section: Introductionmentioning
confidence: 99%
“…The modeling of the extra-delays caused by the atmosphere by the combination of mapping functions and gradients of Eq. (1) has proved very effective since Davis introduced his formula 30 years ago [49][50][51]. But what is the real meaning of effective?…”
Section: Physical Meaning Of Zenithal Delays and Gradientsmentioning
confidence: 99%
“…Some authors [51,55,56] tried to assess the physical meaning of tropospheric gradients, but their effort were limited to qualitative assessments and correlations studies. Up to our knowledge [57], nobody is using gradients as data to constraint operational NWMs, albeit efforts having made to extract gradients from NWM numerical simulations [14] or make comparisons with NWMs outputs [58], or even to propose the use of slant delays for such a use [59].…”
Section: Physical Meaning Of Zenithal Delays and Gradientsmentioning
confidence: 99%
“…GNSS signals propagating from satellites to the ground-based GNSS tracking stations are delayed by the neutral atmosphere (troposphere) [15], [16]. The tropospheric delay over a GNSS station, which is denoted by the zenith total delay (ZTD), together with other geodetic parameters such as site coordinates [17] and tropospheric gradients [18][20], can be accurately estimated from GNSS observations [21][23]. Previous studies have demonstrated that the accuracy of ZTDs obtained from GNSS data processing is about 3−10 mm [19], [24], [25] with a temporal resolution of 5−30 min, i.e., the so-called near real-time (NRT) products.…”
Section: Introductionmentioning
confidence: 99%